Evaluation of pharmacokinetics, bioavailability and urinary excretion of scopolin and its metabolite scopoletin in Sprague Dawley rats by liquid chromatography–tandem mass spectrometry. (8th September 2019) - Li, Bo; Lu, Min; Chu, Zixuan; Lei, Shanshan; Sun, Peilu; Xiong, Shan; Chen, Suhong
Abstract: We aimed to investigate the pharmacokinetics, bioavailability and urinary excretion of scopolin and its metabolite scopoletin in rats. An LC–tandem mass spectrometry (MS/MS) method for simultaneous determination of scopolin and scopoletin in rat biomatrices was developed and validated over a plasma and urine concentration range of 5.0–2000 ng/mL. Chromatographic separation was performed on a Hypersil GOLD C18 column with acetonitrile and 0.1% formic acid in water as mobile phase with gradient elution. Detection was performed in the positive ionization and selected reaction monitoring mode. The intra‐ and inter‐batch precision and accuracy, extraction recovery and matrix effect and stability of scopolin and scopoletin were well within the acceptable limits of variation. There was no gender‐related difference in the pharmacokinetic profiles of scopolin. There were significant differences in total area under the concentration–time curve (AUC), time required to achieve a maximal concentration (Tmax ) and apparent clearance from plasma (Cl/F) of scopoletin between the male and female rats ( p  < .05). The bioavailability (F) of scopolin was exceptionally low. The maximal excretion rates were 7.61 μg/h and 7.15 μg/h for scopolin and 31.68 μg/h and 25.58 μg/h for scopoletin in male and female rats, respectively. The LC–MS/MS method was successfully applied to the pharmacokinetic, bioavailability and urinary excretion studies of scopolin and its metabolite scopoletin following a single administration of scopolin to rats.